Oxidation behavior of Al-doped Ti3SiC2-20 wt.%Ti5Si3 composite. Issue 23 (1st December 2021) - Guedouar, Bendiba; Hadji, Youcef; Benamor, Abdessabour; Chiker, Nabil; Haddad, Adel; Tricoteaux, Arnaud; Erauw, Jean-Pierre; Dupont, Vedi; Hadj-Larbi, Fayçal; Soualili, Mohamed Amine; Hadji, Mohamed
Abstract: In this work, an aluminum-doped Ti3 SiC2 -20 wt.% Ti5 Si3 composite was prepared through reactive spark plasma sintering (SPS) from a powder mixture of Ti, SiC, C, and Al. The microstructure evolution of the formed oxide scales onto this composite were investigated in the temperature range of 1000–1400 °C in air. Up to 1200 °C, the exposed surfaces were highly protected by a continuous and dense α-Al2 O3 layer with a good adherence that acts as a barrier diffusion. Above this temperature, the breakaway oxidation occurs, leading to an oxidation speed-up, which results in a thick oxide scale formation with low oxidation protective capacity. Scanning electron microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), X-Ray Diffraction (XRD), and Raman spectroscopy analysis of the oxide scales at different temperatures revealed that Al2 TiO5 grain growth is the main deterioration factor of the protective α-Al2 O3 layer. The oxidation kinetics of this composite at 1100 °C is comparable with that of the best MAX phases in terms of oxidation resistance, with a parabolic rate constant ( K p ) of 3.08 × 10 −10  kg 2 /m 4 s.